1996
DOI: 10.1007/bf02284842
|View full text |Cite
|
Sign up to set email alerts
|

How to count synapses unbiasedly and efficiently at the ultrastructural level: proposal for a standard sampling and counting protocol

Abstract: After almost 40 years, there is still no consensus on criteria for identifying different types of synapse seen in electron microscopical thin sections or on methods for counting them unbiasedly in 3D. This review proposes a procedure which meets these aims and could be adopted as a standard best-practice sampling and counting convention. It deals exclusively with unbiased stereological methods for counting particles in 3D space because these are efficient and applicable to arbitrary particles regardless of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…The striatum was cut at 60 m on the same day as the perfusion, using a vibratome (The Vibratome Company), and the sections were collected serially into numbered 24-well cell culture plates with 0.1 M PB. Following a random selection of the first section, systematic uniform sampling (as described by Mayhew, 1996;Mouton et al, 2002) was used to select series of equally spaced sections for TH, VGluT1, and VGluT2 immunohistochemistry, and to estimate the total volume of the dorsal striatum.…”
Section: Morphological and Synaptic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The striatum was cut at 60 m on the same day as the perfusion, using a vibratome (The Vibratome Company), and the sections were collected serially into numbered 24-well cell culture plates with 0.1 M PB. Following a random selection of the first section, systematic uniform sampling (as described by Mayhew, 1996;Mouton et al, 2002) was used to select series of equally spaced sections for TH, VGluT1, and VGluT2 immunohistochemistry, and to estimate the total volume of the dorsal striatum.…”
Section: Morphological and Synaptic Studiesmentioning
confidence: 99%
“…Recent work has suggested that in the rat dorsal striatum, there are density gradients for VGluT1 and VGluT2 boutons, and differences in their density in the patch and matrix compartments (Wouterlood et al, 2012). The physical disector is therefore the most appropriate method to count these synapses, since its approach can prevent oversampling of the regions where gradients exist and ensure that patch and matrix compartments have an equal chance of being sampled for every rat (Mayhew, 1996).…”
Section: Morphological and Synaptic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The stereological parameters used for the estimations of total synaptic numbers are shown in Table 2. The synaptic contacts were unequivocally considered as counting units when the pre-and postsynaptic elements were clearly identified, and synaptic vesicles were visualized in at least one of the serial sections (Geinisman et al, 1996;Mayhew, 1996). A mean section thickness of 65 nm was found, based on measurements of 25 folds photographed in each group at a primary magnification of 10,000ϫ (Andrade et al, 1995b).…”
Section: _________________________________ Food Restriction Effects Omentioning
confidence: 99%
“…The serial ultrathin sections stained with lead citrate were used to determine the N V of synapses in the ML of the dentate gyrus, using the physical disector method (Gundersen et al, 1988b;Mayhew, 1996). Briefly, for each tissue block, consecutive ultrathin sections were selected as the reference and look-up sections.…”
Section: Methodsmentioning
confidence: 99%